Introduction to digital systems - Ercegovac, Milo? D.; Lang, Tam?s.; Moreno, Jaime H., 1954- (New York : John Wiley & Sons, 1999)
A basic grounding in one of today's quickly evolving technologies. To gain one's bearing in the whirlwind of rapid development in the digital theory arena, getting a firm grasp of the basics is vital. This book provides a solid foundation in the elements of basic digital electronic and switching theory. Down to earth, yet scholarly in approach, it builds on theory with discussions of real-world digital components, design methodologies, and tools. A companion Web site provides additional information.
Specification of Combinational Systems. -- Combinational ICs: Characteristics and Capabilities. -- Description and Analysis of Gate Networks. -- Design of Gate Networks. -- Specification of Sequential Systems. -- Sequential Networks. -- Standard Combinational Modules. -- Arithmetic Combinational Modules and Networks. -- Standard Sequential Modules. -- Programmable Modules. -- Algorithms and Algorithmic Systems. -- Implementation of Algorithmic Systems. -- Specification and Implementation of a Microcomputer. -- Boolean Algebras. -- Specification Language for Digital Systems. --
Includes index.
1
Keywords: Electronic digital computers; Digital integrated circuits